The Role of Psychological Capital and Leader Member-Exchange on Participatory Budgeting and Managerial Performance - Pradana, Bartolomeus Galih Visnhu (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2021)
The competition is increasingly competitive in the world of education, particularly in this uncertain situation, it encourages every agency to plan, control, and determine the right policies. This study aims to explain the overall relationship between participatory budgeting and managerial performance by including Psychological Capital as an intervening variable and Leader Member Exchange as a moderating variable. The method used was a mixed method with a parallel convergent approach, it is conducted to produce more comprehensive facts. The method of data analysis and hypothesis testing used was Structural Equation Modeling. The survey results of 161 managerial positions in private high schools in DIY indicated that budget participation was directly related to managerial performance. Psychological capital was found to partially mediate the relationship between participatory budgeting and managerial performance. Then, the higher relationship between superiors and subordinates will increase the relationship between participatory budgeting and managerial performance. The survey results were also supported by the results of interviews with informants. This research contributes to the formation of employee of psychological capital and the implementation of leadership style as an important factor in influencing performance.